Antibiotic susceptibility pattern of isolates of Pseudomonas aeruginosa in a Saudi Arabian Hospital (Bangladesh Journal of Medical Science, 2013)
Pseudomonas aeruginosa is one of the most common gram-negative bacteria. identified in the clinical specimens of hospital admitted patients. A major problem in P. aeruginosa infection may be that this pathogen exhibits a high degree of resistance to a broad spectrum of antibiotics. The study aimed to isolate and determine the antimicrobial susceptibility patterns of the P. aeruginosa. This prospective study was done over a period of six months. Forty one clinical isolates of Pseudomonas aeruginosa (P. aeruginosa) were isolated from sputum specimens of the patients suspected of having respiratory tract infection. The antibiotic susceptibility profiles of all the isolates were determined using disk diffusion method as recommended by Clinical Laboratory Standards Institute. Ciprofloxacin was found to be the most effective antimicrobial agent with 85.4% susceptibility followed by imipenem (75.6%), aminoglycosides (amikacin, 95.1% and gentamicin, 90.3%), and the beta-lactams (cefepime 65.8%, ceftazidime, 51.2%). Piperacillin showed the maximum resistance (46.3%) followed by Aztreonam (36.6%). Regular antimicrobial susceptibility surveillance is essential for area-wise monitoring of the resistance patterns. An effective national and state level antibiotic policy and draft guidelines should be introduced to preserve the effectiveness of antibiotics and for better patient management. DOI: http://dx.doi.org/10.3329/bjms.v13i1.17428 Bangladesh Journal of Medical Science Vol. 13 No. 01 January2014: 45-48. Table I & Figure I added on 02 February 2014.